2009
DOI: 10.1109/tbme.2008.2005994
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Monte Carlo Model for the Extraction of Biological Absorption and ScatteringIn Vivo

Abstract: We have a toolbox to quantify tissue optical properties that is composed of specialized fiberoptic probes for UV-visible diffuse reflectance spectroscopy and a fast, scalable inverse Monte Carlo (MC) model. In this paper, we assess the robustness of the toolbox for quantifying physiologically relevant parameters from turbid tissue-like media. In particular, we consider the effects of using different instruments, fiberoptic probes, and instrument-specific settings for a wide range of optical properties. Additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
85
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 28 publications
0
85
0
Order By: Relevance
“…One phantom (Phantom #4) was also chosen as a reference phantom to put the measured and modeled diffuse reflectance on the same scale prior to the inversions. The choice of this reference phantom was based on the comprehensive reference phantom characterization reported by Bender et al [34]. The inverse Monte Carlo model was capable of extracting the optical properties of all pixels in <15 seconds.…”
Section: Tissue Mimicking Phantom Study Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One phantom (Phantom #4) was also chosen as a reference phantom to put the measured and modeled diffuse reflectance on the same scale prior to the inversions. The choice of this reference phantom was based on the comprehensive reference phantom characterization reported by Bender et al [34]. The inverse Monte Carlo model was capable of extracting the optical properties of all pixels in <15 seconds.…”
Section: Tissue Mimicking Phantom Study Resultsmentioning
confidence: 99%
“…Our model can quickly generate optical properties (µ a and µ s ') for a given wavelength-dependent diffuse reflectance and specific probe geometry [35]. Previous studies demonstrating the extraction accuracy and robustness of the model have been reported [24][25][26]34].…”
Section: Monte Carlo Inverse Model Of Diffuse Reflectancementioning
confidence: 96%
See 1 more Smart Citation
“…An inverse MC model 6 was used to extract the a and s Ј of the liquid phantoms. The model was validated in both phantom 6,10 and clinical studies. 7 The MC forward model assumes a set of absorbers ͑oxy-Hb with known extinction coefficients measured using a spectrophotometer in this case͒ are present in the medium.…”
mentioning
confidence: 99%
“…A scalable inverse Monte Carlo model was used to extract tissue scattering, absorption and native fluorescence of 2-NBDG from in vivo optical measurements. The reflectance and fluorescence-based inverse Monte Carlo models have been described in detail previously [97][98][99][100]. Further, the fluorescence model has been validated for both single and multiple fluorophores in the sampled medium [100].…”
Section: Normal Mice and Solid Tumor Studiesmentioning
confidence: 99%